2012
DOI: 10.1038/mt.2012.64
|View full text |Cite
|
Sign up to set email alerts
|

Lentivector Transduction Improves Outcomes Over Transplantation of Human HSCs Alone in NOD/SCID/Fabry Mice

Abstract: Fabry disease is a lysosomal storage disorder caused by a deficiency of α-galactosidase A (α-gal A) activity that results in progressive globotriaosylceramide (Gb(3)) deposition. We created a fully congenic nonobese diabetic (NOD)/severe combined immunodeficiency (SCID)/Fabry murine line to facilitate the in vivo assessment of human cell-directed therapies for Fabry disease. This pure line was generated after 11 generations of backcrosses and was found, as expected, to have a reduced immune compartment and bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…The cDNA of the ΔLNGFR/TMPK component encodes a fusion form of the truncated human low-affinity nerve growth factor receptor (ΔLNGFR) combined with mutant TMPK. ΔLNGFR serves as a cell surface protein marker, and the mutant TMPK induces cell death by downstream-phosphorylating the prodrug 3′-azido-3′-deoxythymidine (AZT) to AZT-DP and, thus, is a “suicide gene” when transduced cells need to be eliminated for any reason 15 . Furthermore, the cDNAs of both the ΔLNGFR/TMPK element and the human GLA sequence were codon-optimized to enhance expression in human cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cDNA of the ΔLNGFR/TMPK component encodes a fusion form of the truncated human low-affinity nerve growth factor receptor (ΔLNGFR) combined with mutant TMPK. ΔLNGFR serves as a cell surface protein marker, and the mutant TMPK induces cell death by downstream-phosphorylating the prodrug 3′-azido-3′-deoxythymidine (AZT) to AZT-DP and, thus, is a “suicide gene” when transduced cells need to be eliminated for any reason 15 . Furthermore, the cDNAs of both the ΔLNGFR/TMPK element and the human GLA sequence were codon-optimized to enhance expression in human cells.…”
Section: Resultsmentioning
confidence: 99%
“…Last year, oral pharmacological chaperone therapy was approved by the European Commission to treat Fabry patients in the European Union (EU) with an amenable mutation of α-gal A 14 . Our group and others have been developing gene therapy for this disorder for nearly 20 years 15, 16, 17, 18, 19, 20, 21, 22, 23. We previously showed that “metabolic cooperativity” or “cross-correction” occurs for Fabry disease.…”
Section: Introductionmentioning
confidence: 99%
“…This solution is stable at 4°C for at least 2 months. [23]. For this study, we analyzed tissues and biological fluids from 24-week-old male NSF mice (n = 9), male NS control mice (n = 2), female NSF mice (n = 9) and female NS control mice (n = 3).…”
Section: Is Preparationmentioning
confidence: 99%
“…In Canada, a clinical trial of gene therapy (FACTs project) for Fabry patients is in progress using recombiRelative distribution of Gb 3 isoforms/analogs in NOD/SCID/Fabry mice tissues determined by tandem mass spectrometry future science group nant lentiviruses targeting hematopoietic stem cells for the sustained systemic correction of the enzyme deficiency [23]. Animal models have been extensively used for the study of human genetic diseases, including for Fabry disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation